The Effect of D-Peptide-B and B.Bifidum Probiotic Lysate on the Expression of TNF-α and IL-1 Genes in AGS Cancer Cell Line Compared to Healthy HEK Cells - Shima Derakhshan; Negar Yavari Tehrani Fard; Nahid Abotalbe; Maryam Naseroleslami (Tehran University of Medical Sciences, 2023)
Background and Aim: Today, natural compounds such as peptides and probiotics can be mentioned as a supplement to the treatment of diseases such as cancer. These compounds may be effective in preventing the progression or treatment of cancer by affecting some molecular pathways including inflammation. The aim of this study was to investigate the effect of D-peptide-B and B.bifidum probiotic lysate on the expression of TNF-α and IL-1 genes in gastric cancer cells of AGS cell line. Materials and Methods: In this study, AGS and HEK cells were cultured in DMEM medium with 10% bovine serum. The cells were treated with different concentrations of D-peptide-B and B.bifidum lysate and were incubated for 24 hours. The cell viability was checked by MTT. For molecular investigations, after RNA extraction and cDNA synthesis, the relative expression of TNF-α and IL-1 genes was evaluated using Real time PCR, and the data were analyzed using statistical methods One-way ANOVA. Results: The MTT results indicated that the AGS cancer cells' survival rate decreased after treatment with dipeptide-B and lysate of B.bifidum as compared to HEK control cells. Furthermore, the study found that the expression levels of TNF-α and IL-1 genes in gastric cancer cells were significantly higher after treatment with D-Peptide-B, bacterial lysate, or both, when compared to normal HEK cells (P≤0.05). Specifically, the IL-1 gene expression increased by 300% (4 times) for peptide treatment, 100% (2 times) for bacterial treatment, and 650% (7.5 times) for combined treatment. Similarly, the TNF-α gene expression increased by 350% for peptide treatment, 100% for bacterial treatment, and 520% for combined treatment. These results suggest that these compounds may have induced cell death in cancer cells by affecting other molecular pathways. Conclusion: Considering that D-peptide-B and B.bifidum lysate had no significant toxicity on normal cells and caused a significant decrease in the survival of cancer cells and this toxicity was dose dependent, therefore, consideration might be given to these natural compounds in treatment of gastric cancer.